Factors Influencing Purchase of Smart Appliances in Smart Homes - K. Maddulety; Suneel Sharma; K. Prasanna Venkatesh; A. Seetharaman (STIE Malangkucecwara, 2017)
Advances in information technology and communications with related computational power are providing a wide spectrum of systems forming the basis of smart home technologies. The appliances with the help of Internet of things (IoT) are used to support the health, safety, and independence of people in smart homes. This research examines the various factors which influence consumers purchase intention of smart appliances. A structural equation was formed using ADANCO modeling tool with the results gained from the consumer questionnaire designed to test the independent variables. Using this, hypotheses are defined and tested. Responses were received from a sample of 302 respondents geographically covering Asia Pacific, America, Australia and Europe. The research shows that all five factors have an impact on the purchase intention with interoperability having the strongest influence followed by privacy & control, technology, awareness and social factor. Therefore, the study implies that smart appliance manufacturers should focus more on the first two factors that are interoperability and privacy & control when communicating with customers which in turn would help them to decide on a purchase.